Representations of the British Soldier : ‘“Mr Lazy’ Pyjamas and “Sobranie Cocktail Cigarettes”. On the Front Line in Helmand with Lewis and his Men.: ‘“Mr Lazy’ Pyjamas and “Sobranie Cocktail Cigarettes”. On the Front Line in Helmand with Lewis and his Men. (2012) - Unknown
No abstract available